2021
DOI: 10.15252/embj.2020106164
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐EM reveals the complex architecture of dynactin's shoulder region and pointed end

Abstract: Dynactin is a 1.1 MDa complex that activates the molecular motor dynein for ultra‐processive transport along microtubules. In order to do this, it forms a tripartite complex with dynein and a coiled‐coil adaptor. Dynactin consists of an actin‐related filament whose length is defined by its flexible shoulder domain. Despite previous cryo‐EM structures, the molecular architecture of the shoulder and pointed end of the filament is still poorly understood due to the lack of high‐resolution information in these reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 78 publications
(164 reference statements)
5
59
0
Order By: Relevance
“…We then determined the crystal structure of human Spindly 1-100 (Table S1; only residues 2-97 were clearly resolved in the electron density), a fragment containing both the CC1 box and the CC1 SCM (Figure 1D-F). The structure demonstrated that Spindly forms a parallel dimeric coiled-coil, similar in its outline to that observed in structures of other adaptors captured in complex with DD (Lau et al, 2021; Urnavicius et al, 2018; Urnavicius et al, 2015). Thus, both Spindly FL and an N-terminal segment of Spindly exist as stable dimers.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…We then determined the crystal structure of human Spindly 1-100 (Table S1; only residues 2-97 were clearly resolved in the electron density), a fragment containing both the CC1 box and the CC1 SCM (Figure 1D-F). The structure demonstrated that Spindly forms a parallel dimeric coiled-coil, similar in its outline to that observed in structures of other adaptors captured in complex with DD (Lau et al, 2021; Urnavicius et al, 2018; Urnavicius et al, 2015). Thus, both Spindly FL and an N-terminal segment of Spindly exist as stable dimers.…”
Section: Resultssupporting
confidence: 64%
“…We next attempted to investigate what forces contribute to maintain Spindly’s autoinhibited state. The pointed end (PE) subcomplex of Dynactin, which interacts with the conserved Spindly motif, has previously been shown to bind adaptors with limited but measurable binding affinity (Gama et al, 2017; Lau et al, 2021; Yeh et al, 2012). Thus, we developed a minimal recombinant adaptor-binding subcomplex of Dynactin, containing only the subunits of the pointed end-capping complex, p25, p27, p62 and Arp11 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 ) and robust dynein–dynactin complex motility in vitro ( Schroeder and Vale, 2016 ). A popular hypothesis suggests the pointed-end complex protein p25 contains a mutually exclusive binding site that either binds a Spindly motif or the tail of autoinhibited p150; therefore, activator binding to p25 releases p150 from autoinhibition ( Cianfrocco et al, 2015 ; Schroeder and Vale, 2016 ; Qiu et al, 2018 ; Lau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%